HAZARD IDENTIFICATION USING THE HAZARD IDENTIFICATION AND RISK ASSESSMENT AND DETERMINING CONTROL (HIRADC) TECHNIQUE (CASE STUDY AT LABORATORIES AT UNIVERSITAS ISLAM NEGERI SUMATERA UTARA) - Nabila Syahlan (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2021)
Every workplace has a risk of accidents and health problems. The university is a workplace that has a variety of laboratories with a variety of risks, so prevention and control efforts are needed to prevent accidents and health problems for lecturers, staff, and students. Prevention and control efforts are attempts to build a culture of Occupational Safety and Health (OSH) in Higher Education. This study was conducted to determine the type of hazard, risk assessment based on the source of danger and risk assessment based on the type of hazard in all laboratories at UINSU. Hazard identification and risk assessment were analyzed with Hazard Identification and Risk Assessment and Determining Control (HIRADC) Technique. The identification results obtained by sources of hazards in the form of chemical hazard. Public Health Science Faculty has 2 sources of potential hazard in high risk level and 2 sources of potential hazards in high risk level were in Science and Technology Faculty. It is expected that the identification results can be evaluated and used as reference material to determine efforts to repair and control the risk of hazards in the laboratory at UINSU. The laboratories need to have guidelines and procedures for Occupational Safety Health.